2011
DOI: 10.1007/s00167-011-1412-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of additional gracilis tendon harvest on muscle torque, motor coordination, and knee laxity in ACL reconstruction

Abstract: Prospective comparative study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 24 publications
0
61
0
2
Order By: Relevance
“…Seven were classified as good,43 45–47 53 55 66 26 as fair3 5–9 21 23 37–39 41 42 44 48–50 52 54 56 60–67 and 6 as poor 29 40 51 57–59. Thirty studies did not include all important adverse events that could have an effect on the intervention reported (criterion 8),5–7 9 21 23 29 38–40 42–52 54 56 57 59 60 63 64–67 23 studies did not adequately describe the source population and how they were recruited (criterion 11 and 12),3 5 6 8 21 37–40 42 44 48–52 54 57–60 64 65 24 studies did not describe if the source population was recruited in the same time period (criterion 22),3 8 9 23 29 37–42 44 48–52 54–58 63 64 66 and 29 studies did not report sample size calculation (criterion 27) 3 6–8 21 23 29 38–44 49–53 56–61 63–67. Other criterion, such as criterion 22 and 23, were not commonly fulfilled due to most studies not being randomised, while criterion 14 and 15 were not commonly reported due to lack of blinding.…”
Section: Resultsmentioning
confidence: 99%
“…Seven were classified as good,43 45–47 53 55 66 26 as fair3 5–9 21 23 37–39 41 42 44 48–50 52 54 56 60–67 and 6 as poor 29 40 51 57–59. Thirty studies did not include all important adverse events that could have an effect on the intervention reported (criterion 8),5–7 9 21 23 29 38–40 42–52 54 56 57 59 60 63 64–67 23 studies did not adequately describe the source population and how they were recruited (criterion 11 and 12),3 5 6 8 21 37–40 42 44 48–52 54 57–60 64 65 24 studies did not describe if the source population was recruited in the same time period (criterion 22),3 8 9 23 29 37–42 44 48–52 54–58 63 64 66 and 29 studies did not report sample size calculation (criterion 27) 3 6–8 21 23 29 38–44 49–53 56–61 63–67. Other criterion, such as criterion 22 and 23, were not commonly fulfilled due to most studies not being randomised, while criterion 14 and 15 were not commonly reported due to lack of blinding.…”
Section: Resultsmentioning
confidence: 99%
“…Anatomically reconstruction of the ACL is considered a gold standard in the world of orthopedics as it provides a facile graft placement, better outcomes and lower pain after surgery. The most common graft used in all-inside technique is the quadrupled semitendinosus tendon, therefore preserving hamstring strength and allowing a faster rehabilitation and return to daily activities [3,12,13].…”
Section: Resultsmentioning
confidence: 99%
“…Fixations were made with two adjustable cortical-loops in the all-inside group and one adjustable cortical-loop and one bioresorbable interference screw for the full tibial tunnel, thus providing superior mechanical resistance and avoidance of the aforementioned complications. In a prospective study on 150 patients Lubowitz et al found no differences between all-inside and full tibial tunnel ACL reconstruction techniques [12]. The team also evaluated other scores, narcotic consumption, tibial and femoral widening but with differences between the groups only regarding VAS pain score.…”
Section: Resultsmentioning
confidence: 99%
“…The all-inside modification of the translateral technique requires only isolated harvesting of the semitendinosus tendon, which has previously been shown to preserve postoperative hamstring strength, 16 and allows the remaining hamstring to function as a secondary stabilizer or to be used as a graft for further ligament reconstructions. The use of bicortical suspensory fixation of the graft has also been shown to withstand higher force to failure over conventional interference fixation devices (data on file at Arthrex).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4 shows the anatomic footprint with the relevant measurements annotated. Two measurements are made; the first is made by use of the long axis of the measuring tool that measures from deep to shallow with the center of the ACL footprint at the midpoint, 16 which corresponds to the bifurcate ridge. A second measurement is then made using the calibrated tip that determines the height of the center of the The lateral portal should be placed as close to the patellar tendon as possible to allow easy passage of the translateral instruments.…”
Section: Techniquementioning
confidence: 99%